Adsorption of Humic Acid from Aqueous Solution on Single-Walled Carbon Nanotubes - Moussavi, S.P.; Ehrampoush, M.H.; Mahvi, A.H.; Ahmadian, M.; Rahimi, S. (Asian Journal of Chemistry, 2013)
Humic acid is one of the most important components of humic substances. Its presence in water doesn't directly cause toxicity but can indirectly cause undesirable effects on appearance and taste of water. It can also result in production of undesirable and hazardous products known as disinfectant by-products. In this research, adsorption of humic acid was examined using single-walled carbon nanotubes (SWCNTs). Also, the effect of effective parameters on adsorption process including adsorbent dose, initial concentration of humic acid, contact time and initial solution pH were evaluated. According to results, as pH increases, humic acid adsorption increases too. Also, as adsorbent dose and contact time increase, the absorption of humic acid increases too. Results obtained from this study revealed that single-walled carbon nanotubes are able to remove humic acid completely in different concentrations. Therefore, it can be concluded that single-walled carbon nanotubes are considered powerful adsorbents for removing humic acid from aqueous solutions.